PENINGKATAN PRODUKSI SERTA MANAJEMEN PAKAN BERPROTEIN TINGGI BERBAHAN DASAR MAGGOT DALAM MENJAGA KETAHANAN DAN PAKAN MANDIRI PETERNAK KAMBING : PENINGKATAN PRODUKSI SERTA MANAJEMEN PAKAN BERPROTEIN TINGGI BERBAHAN DASAR MAGGOT DALAM MENJAGA KETAHANAN DAN PAKAN MANDIRI PETERNAK KAMBING - AMRAN, MUHAMMAD; Alkhalidi, Ahmed; Syakir, Ahmad (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Feed security is an important aspect in supporting the sustainability of goat farming businesses, especially in rural areas that depend on local resources. This service aims to improve the production and management of high-protein feed made from Black Soldier Fly maggot in the Beusare Maju Livestock Group. Maggot is known to have a high protein content, so it has great potential as an independent and cheap alternative feed ingredient. The service methods used include maggot cultivation training, making high-protein feed formulations, and feeding management for goats. The results of this activity are expected to be able to increase the productivity of goat farming, reduce feed costs, and strengthen the independence of farmers in providing quality feed. The implementation of maggot cultivation technology also contributes to the reduction of organic waste in the surrounding environment. As a result, there has been an increase in the welfare of farmers through a decrease in operational costs and an increase in livestock production. The results of the observation percentage after the evaluation of Beusare Maju goat farming are not much different from the expected percentage of results. In terms of improving feed management capabilities, an average of 85% from 100% and an increase in feed quantity was obtained an average of 77.5% from 100%. .